POF Handbook Optical Short Range Transmission Systems - Ziemann, Olaf; Krauser, Jürgen; Zamzow, Peter E.; Daum, Werner (Springer Berlin Heidelberg : Imprint: Springer, 2008)
One half decade after the first edition the book is now published in a completely new revision, updated and doubled in size. The Polymer Optical Fiber Application Center of the University of Applied Science was responsible for this second edition. A huge number of measurements of bandwidth, optical properties and the possible transmission capacities of more than a dozen large diameter fiber versions are included. Many internationally published results are shown in the new edition. The POF was a niche technology only a few years ago. In the meantime, millions of cars drive with POF onboard networks. Due to the rapidly growth of the number of private broadband access lines and the increase in the available bit rate at the same time, mainly driven by IP TV applications, the POF will be used in home networks more and more. This handbook shows available commercial solutions as well as the potentials for future applications. Further application areas are optical waveguides, POF as low cost sensors and multi parallel data connections. More than 1000 figures, 600 references and numerous tables complete the text.